EFEKTIVITAS CAPAIAN KOMPETENSI BELAJAR SISWA DALAM PEMBELAJARAN SAINS DI SEKOLAH DASAR - Yanti Fitria (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2017)
This study aimed to describe effecitivity of the learning outcome IPA using inquiry method. This type of research is the Classroom Action Research (CAR). Research procedures conducted through four stages, namely planning, implementation, observation, and reflection. The study uses a qualitative and quantitative approach. Subjects were teachers and students of fourth class in elementary school 08 Padang City. Data was obtained from the results of observations and test results of learning. The research was conducted by two cycles and each cycle consisting of two meetings. The results of the research that has been conducted every cycle seen an increasein the average value of student learning outcomes are: (a) the cognitive aspects of 75 to 93, (b) the affective aspects of 74 to 95, and (c) psychomotor aspects from 76 to 94. It can be concluded that the CAR using the inquiry method can improve learning outcomes of science fourth grade students of fourth class in the state elementary school 08 Padang City.Key words: Learning competency; science learning; inquiry method